Short duration high-intensity interval taekwondo training substantially improves body composition and physical fitness in previously-trained individuals: a proof-of-concept study - Mathunjwa, M.; Shaw, B.; Mugandani, S.; Shaw, I.; Djarova, T. (Archives of Budo, 2020)
Background and Study Aim: Professional taekwondo (TKD) athletes possess below average body fat percentages and the overall winners at the Sydney 2000 Olympic Games had a lower body mass index (BMI). Further, physical fitness remains one of the main factors for success in TKD. This indicates the importance of managing body composition and physical fitness for TKD performance. This study`s aim was to generate knowledge about the effect of a four-week high-intensity intermittent TKD and strength training conditioning program on body composition and physical fitness of South African TKD athletes.